Windtalkers - Woo, John (Quezon City : Viva Video, 2002)
In the brutal World War II Battle of Saipan, Sergeant Joe Enders Academy Awards Winner Nicolas Cagel guards - -and ultimately befriends - - Ben Yahzee (Adan Beach), a young Navajo trained in the one wartime code never broken by the enemy, the Navajo code. But it Yahzee should fall into Japanese hands, how far will Enders go to save the military's most powerful secret? John Woo directs this "exciting" {Premiere] "against-all-odds battle adventure" [The Toronto Star] written by John Rice and Joe Batteer and inspired by the true story of the Navajo soldiers whose courage and sacrifices helped win the war in the Pacific